Optimizing the Application of Artificial Intelligence in High School Learning Communication Strategies - Daniari Setiawati; Ahmad Fitriasari; Ni Putu Limarandani (Yayasan Ilomata, 2026)
The accelerated integration of Artificial Intelligence (AI) into educational ecosystems presents profound opportunities for pedagogical transformation, particularly within Senior High School (SMA) environments. This study investigates the optimization of AI applications in mediating learning communication strategies operationally defined herein as the facilitation of purposeful, bidirectional feedback loops, the structuring of adaptive interaction patterns, and the refinement of instructional messaging. Employing a qualitative mixed-methods design, this research triangulates a systematic literature review with a thematic analysis of semi-structured stakeholder interviews involving school leadership, instructional staff, and counseling professionals. The findings suggest that AI can enrich learning communication by dynamically adjusting instructional messaging and providing real-time, bidirectional feedback to students, thereby supporting constructivist knowledge building. Applications such as chatbot-based conversational agents, adaptive learning algorithms, and automated content generation tools are reported to facilitate greater efficiency in material delivery while affording students personalized learning pathways. However, the study identifies critical structural constraints, noting that successful implementation within the SMA context is heavily contingent upon infrastructural readiness, the mitigation of the digital divide, and the comprehensive development of teachers' digital pedagogical literacy. The authors conclude that while AI holds significant potential to make learning communication more inclusive and data-driven, causal impacts on long-term achievement require further quantitative evaluation. Therefore, it is crucial for educational institutions to develop comprehensive, human-centered governance policies that support the sustainable and ethical integration of this technology.